Reflective Thinking Reflective Thinking Ability of Junior High School Students in Solving Problems Involving Systems of Linear Equations in Two Variables: Kemampuan Berpikir Reflektif Siswa SMP dalam Memecahkan Masalah Sistem Persamaan Linear Dua Variabel - Anindia Putri Azahra (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
This study aims to describe the profile of students' mathematical reflective thinking in solving problems related to systems of linear equations in two variables (SLETV). The research employed a mixed-methods approach and was conducted at a junior high school in Bandar Lampung. The subjects consisted of 60 eighth-grade students. The students' test responses were analyzed, and three representative students each corresponding to one of the phases of mathematical reflective thinking related to SLETV were selected for interviews. The instruments used in this study included three items designed to assess mathematical reflective thinking ability and an interview guideline. The data were analyzed based on the phases of mathematical reflective thinking, namely reacting, comparing, and contemplating. The results indicated that the percentage of students' reflective thinking profiles was categorized as good in the reacting phase, good in the comparing phase, and fairly good in the contemplating phase.